Heteromeric Anopheline odorant receptors exhibit distinct channel properties. - Gregory M Pask (Public Library of Science (PLoS), 2011)
Background Insect odorant receptors (ORs) function as odorant-gated ion channels consisting of a conventional, odorant-binding OR and the Orco coreceptor. While Orco can function as a homomeric ion channel, the role(s) of the conventional OR in heteromeric OR complexes has largely focused only on odorant recognition. Results To investigate other roles of odorant-binding ORs, we have employed patch clamp electrophysiology to investigate the properties of the channel pore of several OR complexes formed by a range of different odorant-specific Anopheles gambiae ORs (AgOrs) each paired with AgOrco. These studies reveal significant differences in cation permeability and ruthenium red susceptibility among different AgOr complexes. Conclusions With observable differences in channel function, the data support a model in which the odorant-binding OR also affects the channel pore. The variable effect contributed by the conventional OR on the conductive properties of odorant-gated sensory channels adds additional complexity to insect olfactory signaling, with differences in odor coding beginning with ORs on the periphery of the olfactory system.